Hambatan Komunikasi Mahasiswa Rantau Suku Menui: Studi Kasus Pada Mahasiswa Universitas Tadulako - Hasan, Muhammad Fajrin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
he purpose of this study was to determine the barriers to intercultural communication that occurred in the Menui tribal students at Tadulako University. The type of research used is descriptive qualitative. Data collection techniques were carried out by means of observation and in-depth interviews. There were 6 informants in this study. The data collection techniques used were observation, in-depth interviews, and documentation. The data analysis technique used is interactive analysis, namely data reduction, data presentation, and drawing conclusions. Based on the results of research in general, it shows that language differences are one of the obstacles experienced by Menui ethnic students because of the limitations experienced by communication actors, causing a lack of self-disclosure so that they feel foreign to themselves among the culture they have just experienced. Barriers due to stereotyped prejudice and the tendency to judge the Menui ethnicity which results in differences in perspective or perception in assessing a habit due to cultural differences, resulting in barriers to intercultural communication. High anxiety, due to lack of self-confidence and concerns about not being accepted by other cultures, causes anxiety for communicators to share their opinions with each other.